2020
DOI: 10.1177/0044118x20918435
|View full text |Cite
|
Sign up to set email alerts
|

Why Do We Drop Out? Typology of Dropping Out of High School

Abstract: We assessed how high school dropouts in Croatia interpret their school experiences and life circumstances, using semi-structured interviews of 20 young people, M ( SD) = 18.4 (1.23) years, 63.6% male, based on questions following a chronological life course from elementary to high school. Using qualitative content analysis and cluster analysis, we yielded a typology of high school dropouts. Four high school dropout types were identified based on the factors leading to dropout: (a) the poor academic achievers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
1
17
0
2
Order By: Relevance
“…This procedural concept of dropout has been backed by some of surveys (e.g. Nand, 2017;Ogresta, Rezo, Kožljan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This procedural concept of dropout has been backed by some of surveys (e.g. Nand, 2017;Ogresta, Rezo, Kožljan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other reasons included lack of motivation to study, low academic performance, parents' disinterest in their children's learning, and unhappy families (e.g., parents' divorce status). The other reasons derive from families including unhappy families, difficult economic status, or the living condition of students (Randolph et al, 2006;Rumberger & Lim, 2008;Goulet et al, 2020;Ogresta et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Others, as Le and Tran (2013) and Pham and Thach (2016), also showed that poor academic performance and lack of learning motivation were the most popular of dropping out of school. Moreover, recent studies on the relationship between academic performance and dropping out of school by Goule et al (2020), andOgresta et al (2020) and Stevenson et al (2021), have determined that students' academic performance have a great influence on going to school or not. Besides, different problems from schools were introduced in Ralph (1997), such as focusing on academic achievement, focusing on teaching, in Rumberger and Lim (2008) attributed to factors related to students' individual characteristics.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Slično, primjerice, za jedan dio NEET populacije u hrvatskom kontekstu, one koji ispadaju iz sustava obrazovanja, recentno istraživanje navodi da su heterogena populacija i naglašava kompleksnost fenomena(Ogresta et al, 2020).…”
unclassified